2022
DOI: 10.3390/nu14224812
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health-Promoting Behaviors and Their Association with Weight Loss, Retention, and Engagement on a Digital Program: Prospective Study

Abstract: Health-promoting lifestyle behaviors (e.g., as measured by the HPLP-II) are associated with reductions in lifestyle disease mortality, as well as improved well-being, mental health, and quality of life. However, it is unclear how a weight-management program relates to a broad range of these behaviors (i.e., health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management), especially a fully digital program on which individuals have to self-manage their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…This research was limited by the fact that the provision of the scale was not individually randomized but the result of insurance providers’ choice to provide or not provide scales. In addition, although findings from past research show that both self-weighing and retention are associated with weight loss [ 4 , 5 , 7 ], suggesting that the provision of a scale might also be related to weight loss, this question was outside the scope of this analysis. This preliminary study is timely, given the increasing importance of understanding and attenuating the high rates of attrition in digital health [ 8 - 10 ], and might assist insurance providers to weigh the cost of provisioning a scale to the benefits of increased retention in lifestyle behavioral programs.…”
Section: Discussionmentioning
confidence: 98%
“…This research was limited by the fact that the provision of the scale was not individually randomized but the result of insurance providers’ choice to provide or not provide scales. In addition, although findings from past research show that both self-weighing and retention are associated with weight loss [ 4 , 5 , 7 ], suggesting that the provision of a scale might also be related to weight loss, this question was outside the scope of this analysis. This preliminary study is timely, given the increasing importance of understanding and attenuating the high rates of attrition in digital health [ 8 - 10 ], and might assist insurance providers to weigh the cost of provisioning a scale to the benefits of increased retention in lifestyle behavioral programs.…”
Section: Discussionmentioning
confidence: 98%
“… 46 The app has several key features of success that we identified, including Cognitive Behavioral Theory grounding. 47 …”
Section: Discussionmentioning
confidence: 99%
“…We speculate that Noom Weight users may have shown significant cost savings compared with non-Noom Weight users because weight management efforts reduced the incidence of chronic conditions and their associated medical costs [42][43][44]. We also speculate that Noom Weight's educational content on healthy behaviors could result in improved medication adherence, especially because a previous study found that Noom Weight users' health responsibility (eg, taking interest in, and responsibility for, their overall physical health) improved over the course of the program [32,45]. However, because this study did not test causal pathways, future research should test and identify potential mechanisms.…”
Section: Comparison With Prior Workmentioning
confidence: 90%
“…At 24 months after the index date, 0.04 fewer inpatient visits, 0.58 fewer outpatient visits, 0.01 fewer surgeries, and 3.13 fewer prescriptions were recorded among Noom Weight users compared with non-Noom Weight users. Noom Weight users had higher use of telehealth services at 12 months after the index date (MD 0.02/user), perhaps because of increased connectivity to digital health services owing to their use of Noom Weight or because of increased health responsibility as a result of the program [32]. There were also a greater number of obesity-specific prescriptions for Noom Weight users compared with non-Noom Weight users at 12 months (MD 0.08/user), which may be related to more health-conscious behavior [32] among newly registered Noom Weight users, potentially leading to higher rates of prescriptions.…”
Section: Principal Findingsmentioning
confidence: 99%